Inflamabilidad de combustibles forestales muertos presentes en el bosque andino del Parque Universitario “Francisco Vivar Castro”, Loja, Ecuador - Troya Abad, Jackson Alejandro (2023)
Natural forests are ecosystems that are increasingly prone and vulnerable to the occurrence of forest fires, even more so when there is a significant load or quantity of live and dead forest fuels with different characteristics or capacities to ignite. The objective was to contribute to the knowledge of fire behavior by studying the flammability of dead forest fuels through the determination of their characteristics and flammability category under laboratory conditions. The study was carried out in the Andean forest of the Francisco Vivar Castro University Park. Fine, light and medium dead forest fuels and leaf litter were selected. The sample unit consisted of a weight of 10 grams, with 50 replicates per fuel. The flammability characteristics evaluated were: ignition time, sustainability, combustibility and flame height. The samples were evaluated by means of an epiradiator at a fixed temperature of 350 °C for litter and fine fuels, 375 °C for light fuels, and in medium fuels at 420 °C by means of the direct flame method. The flammability category was determined by means of the Valette and Hachmi methods, allowing us that the dead forest fuels presented categories from very slightly flammable to extremely flammable. The litterfall presented a category of extremely flammable, the fine fuel was categorized as low flammable and very extremely flammable, the light fuel resulted in very low flammable and very extremely flammable, the medium fuel presented a category of very low flammable. The litter had the shortest ignition time (15.84 s), lowest sustainability (46.48 s), highest flame height (64.06 cm) and highest combustibility (0.21g/s) with respect to the other fuels. On the other hand, the medium fuels presented the following averages: longer ignition time (170.46 s), higher sustainability (144.74 s), combustibility (0.07 g/s) and flame height (15.32 cm) were the lowest with respect to the rest of the fuels. The flammability categories are promising results because they constitute an important advance in the knowledge of fire behavior, ecology and management, allowing to initiate the study at the species and ecosystem level. Keywords: combustibility, fire, ignition, flammability, sustainability.